Pengaruh Meditasi Memaafkan Terhadap Peningkatan Life Satisfaction Dengan Mengembangkan Konsep Diri, Regulasi Emosi, dan Aktualisasi Diri Pada Ibu Rumah Tangga di Wisuda Yoga Kabupaten Klungkung - Ni Luh Ayu Martini; I Wayan Nerta; I Gusti Made Widya Sena (Jurnal Yoga dan Kesehatan, 2022)
Life Satisfaction can be felt by everyone, including a woman in assistance as a housewife. The role of a woman in life is very complex. In increasing life satisfaction, women in the role of housewives can carry out various activities that can support improving the quality of life as currently being discussed, namely the practice of meditation. One of the places to practice yoga and meditation in Bali, namely Wisuda Yoga, Klungkung Regency, has a healing process that is focused on medical practices that lead to the healing process in order to achieve life satisfaction.This study aims to determine the stages of the practice of forgiveness and its effect on the life satisfaction of housewives at Wisuda Yoga, Klungkung Regency. This research lasted for one month. This type of research is a quantitative study, using a pre-experimental design with a one-group pre-post-test design. The total population is 30 people. The sample in this study collected 28 respondents aged 24 to 44 years, this number of samples used the formulation of Isaac and Michael with an error rate of 5%. The statistical test results in this study were 0.000 which proved that there was a justifiable effect on the life satisfaction of housewives at Wisuda Yoga, Klungkung Regency. The results of the effective test also provide reinforcement regarding the results of this study because the effect size obtained is 0.88, which indicates that the practice of agreeing provides great effectiveness for increasing life satisfaction for housewives at Wisuda Yoga Klungkung Regency.